Social media marketing-based brand engagement strategy in increasing purchasing decisions in fashion SMEs in Bali - Giantari, I Gusti Ayu Ketut; Sukawati, Tjok Gede Raka; Ekawati, Ni Wayan; Yasa, Ni Nyoman Kerti (Edelweiss Applied Science and Technology, 2025)
The development of very fast fashion trends and the entry of foreign competitors have an impact on consumer purchasing decisions, especially for Generation Z (Gen Z) in fashion MSMEs in Bali. To encourage increased consumer purchasing decisions, social media marketing is used as a form of promotion through Instagram, Facebook, email marketing, WhatsApp, and TikTok. From several previous research studies on the impact of social media marketing on purchasing decisions, the results of the studies are still inconsistent (research gap). To fill this research gap, brand engagement and brand trust strategies are used as mediators for fashion MSMEs to increase consumer purchasing decisions. The purpose of the study was to test and explain brand engagement strategies based on social media marketing to increase Gen Z purchasing decisions in fashion MSMEs in Bali. This study uses a quantitative approach with 200 respondents from Gen Z who made fashion product purchases using a non-probability sampling method, namely purposive sampling. Data collection uses a survey method, specifically a questionnaire given to both offline and online respondents. The research instrument was tested for validity and reliability, and the data analysis technique used descriptive statistical analysis and inferential statistics (SEM-PLS). The research results imply that they can enrich the theory of planned behavior in the context of fast fashion. The practical implications are that fashion SMEs in Bali should design interesting content on social media, create their products well from quality materials, and always ensure the quality of ready-to-wear clothing and services so that they maintain a good image.